(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Astiani D, Mujiman, Curran LM. 2017. Trees of tropical peatland forest influence on variability of water and carbon input through stemflow. Biodiversitas 18: 383-388. Hydrology controls the chemical and biotic processes in peatlands, influencing interactions among vegetation, nutrient dynamics, and carbon fluxes. The effects of forest degradation revealed severe changes in the hydrological cycle such as variability of water input on forest floor, soil water storage and the ability to abstract water from soil depth. A study had been conducted to investigate part of the water cycle, the amount of water and carbon input through stemflow into peatland forest floor for 2 years. Stemflow was measured on 20 trees of each 3 blocks of forest with tree diameter ranging from 10-30 cm dbh using stemflow collectors. Then the trees were grouped to three bark types (smooth, mid, and coarse) to investigate whether it had influenced the inputs. Results showed that with mean annual precipitation of 3282 Â± 128mm, annual mean stemflow for the area was 18.2% of the rainfall. Further analysis demonstrated that tree species with smoother bark textures tend to bring more water to forest floor compared to mid and coarse bark textures (46% and 42.5% more than coarse and intermediate consecutively). The carbon input also show similar trend. The results implied that tree species influence the amount of stemflow and significant amount of water could be slower down come to forest floor through this mechanism and protected forest soil. Keywords: Annual stemflow, peatland forest, hydrological flow, tree barks, tree species